Mesopelagic Scattering Layer Behaviors Across the Clarion-Clipperton Zone: Implications for Deep-Sea Mining - Perelman, Jessica N.; Firing, Eric; van der Grient, Jesse M. A.; Jones, Benjamin A.; Drazen, Jeffrey C. (Frontiers in Marine Science, 2021)
The Clarion-Clipperton Zone (CCZ) is a 4 million km2 area in the eastern Central Pacific Ocean exhibiting large variability in environmental parameters, particularly oxygen and primary production, that is being targeted for deep-sea polymetallic nodule mining. This remote region’s pelagic biology is very poorly sampled, including for micronekton and zooplankton that provide essential ecosystem services such as carbon flux and support for commercial fisheries. We built a baseline of deep scattering layer (DSL) depths and vertical migration behaviors, proxies for mesopelagic micronekton and zooplankton communities, using shipboard acoustic Doppler current profiler datasets. Acoustic data (38 kHz, 75 kHz) were compiled from research cruises passing near or through the CCZ (2004–2019), and environmental data (mean midwater oxygen partial pressure, surface chlorophyll-a, and sea surface height anomaly) were assembled from the World Ocean Atlas and satellite oceanographic datasets. Our results suggest that midwater oxygen, associated with the Eastern Tropical Pacific Oxygen Minimum Zone (OMZ), is the strongest predictor of daytime DSL depths and the proportions of midwater populations that undergo vertical migration in this region. We used these relationships to predict micronekton and zooplankton behaviors across the CCZ, including licensed mining exploration areas and no-mining reserves. While the OMZ encompasses most licensed exploration areas, the current network of reserves lies outside of the core OMZ and ultimately may not represent or protect the pelagic OMZ fauna at highest risk from mining impacts. This research will further assist in developing resource exploitation regulations by the International Seabed Authority, and will provide mesopelagic baseline information for monitoring changes that may occur in the CCZ once industrial-scale mining begins.